Daňové aspekty a výhodnost zaměstnaneckých benefitů - Nováková, Michaela (Vysoké učení technické v Brně. Fakulta podnikatelská, 2025)
Bakalářská práce se zaměřuje na účetní a daňové aspekty zaměstnaneckých benefitů. Teoretická část práce definuje pojem motivace, detailně popisuje zaměstnanecké benefity a jejich poskytování v souladu s právními předpisy. V prakticke casti jsou analyzovane zamestnanecke benefity u vybrane spolecnosti a take je vypracovan navrh na optimalizaci techto benefitu.

The bachelor's thesis focuses on the accounting and tax aspects of employee benefits. The theoretical part of the thesis defines the concept of motivation, provides a detailed description of employee benefits, and examines their provision in accordance with legal regulations. The practical part analyzes employee benefits in a selected company and presents a proposal for optimizing these benefits.
Tax aspects and convenience of employee benefits
Keywords: Zaměstnanecké benefity; daňové náklady; účetnictví; motivace; odměňování.; Employee benefits; tax expenses; accounting; motivation; remuneration.